Variations in nutrients and microbes during the occurrence and extinction of algal blooms: A mesocosm experiment with the addition of marine aquaculture sediment - Sun, Yuanmin; Tang, Kunxian; Ma, Yong; Zhu, Xuan; Li, Heyang; Zhang, Fei; Chen, Shan; Huang, Haiping (Frontiers in Marine Science, 2022)
The release of pollutants in sediment often causes secondary pollution of seawater. In this paper, marine aquaculture sediment was added to seawater in a coastal land–based mesocosm, and the changes in microbial and physicochemical parameters were measured to study the influence of sediment disturbance on seawater. The results showed that sediment disturbance had adverse effects on seawater. After adding and stirring the aquaculture sediment, the concentration of dissolved oxygen (DO) gradually decreased, and those of nutrients gradually increased; in particular, the concentrations of ammonia and dissolved inorganic phosphorus (DIP) increased most sharply. After day 9, a bloom dominated by Chaetoceros occurred. Concentrations of chlorophyll a (Chl-a) increased, and two obvious Chl-a peaks were observed; the trends of DO and pH were similar to that of Chl-a during the bloom period; and DIP and ammonia were exhausted during periods of Chl-a peaks. During the extinction of algal blooms, the concentrations of Chl-a and DO decreased, whereas those of DIP and ammonia increased. The variation trends of bacteria and viruses were similar to that of Chl-a, with two obvious peaks, which were later than those of Chl-a. There were close connections between Chl-a and nutrients, bacteria and viruses and they showed a trend of changes in turn from nutrients to phytoplankton to bacteria to viruses during the experiment. We concluded that bloom formation was mainly affected by nutrients and weather, and the main reason for bloom decline was the depletion of nutrients. The increase in zooplankton, bacteria, and virus abundance was the ecological effect after the occurrence of algal blooms, and they affected the development of algal blooms.